Pelatihan Pemantauan Status Gizi Balita pada Kader Posyandu di Wilayah Kerja Puskesmas Blang Mangat Kota Lhokseumawe - Elizar, Elizar; Iswani, Rayana; Putri, Hendrika Wijaya Kartini; Seriana, Irma (Universitas Baiturrahim, 2025)
Malnutrition, in all its forms, includes undernutrition (wasting, stunting, underweight), vitamin or mineral deficiencies, overweight, obesity, and non-communicable diseases caused by diet. Nearly half of deaths in children under 5 years of age are caused by malnutrition. The active role of cadres in early detection of malnutrition and stimulation of growth and development in children at the Integrated Health Post (Posyandu) contributes to reducing the prevalence of malnutrition and thus improving the quality of health. This community service activity trained Posyandu cadres to monitor the nutritional status of toddlers in the Blang Mangat Lhokseumawe Community Health Center (Puskesmas) working area. The problem-solving method was carried out through education, training on measuring nutritional status and filling out the Health Card (KMS). Activities included outreach, pre-tests, group discussions, training, post-tests, and mentoring. Cadres were trained to measure the height and weight, upper arm circumference, and head circumference of toddlers, and to fill out the KMS. The assessment results revealed that the cadres' understanding of how to measure nutritional status and fill out the Health Card (KMS) improved significantly, with 100% coverage, and 80% of them were able to carry out the nutritional status measurements correctly. Observations during the cadre skills training at the integrated health post (Posyandu) showed that all cadres were able to accurately measure the nutritional status of toddlers. This demonstrates active participation and the practical application of the knowledge gained during the training. Improving cadre skills through ongoing training is crucial for monitoring toddler nutritional status.